Propeller blade stress analysis using CATIA - Syed Mohamed Ali, Jaffar; Mokhtar, Mohammad Solehan (IIUM Press, 2011)
A procedure for modeling and stress analysis of a propeller blade using CATIA software have been detailed. The blade has been modeled with its twist angle and the results for different material have been presented graphically.